Solid-liquid equilibrium of 3,3-dilauryl thiodipropionate/lauryl alcohol in melt crystallization and model based process design - Pan, De-Tao; Yan, Wei-Cheng; Luo, Zheng-Hong (Chemical engineering science, 2022)
[Display omitted] •Phase diagram of 3,3-dilauryl thiodipropionate (DLTP) and lauryl alcohol (LA) binary system was determined.•Feasibility of melt crystallization for the separation of DLTP and LA was evaluated for the first time.•Performances of three models were evaluated based on solid-liquid equilibrium data.•A multi-stage melt crystallization configuration was proposed.•3 stages with keff ≤ 0.4 are required to obtain the 99% (mass fraction) DLTP product. Melt crystallization is a promising and widely used method for obtaining pure compounds. Nonetheless, separation of 3,3-dilauryl thiodipropionate (DLTP) has not yet been realized by melt crystallization. Solid-liquid equilibrium is the fundamental for the separation process design. In this work, we evaluated the feasibility of the purification of DLTP from the DLTP/lauryl alcohol (LA) binary mixture by melt crystallization technique. For this purpose, the solid-liquid equilibrium data were measured using differential scanning calorimetry (DSC) technique. The experimental data were correlated by Wilson, Margules-3-suffix and Non-Random Two-Liquid (NRTL) activity coefficient models to obtain the binary parameters of the three models. Eutectic composition and temperature were calculated using NRTL model, which were xLA = 0.961 (molar fraction) and 295.79 K, respectively. On the basis of the solid–liquid equilibrium, the multistage countercurrent separation configurations were proposed for the separation of the binary system. The formulated Mixed Integer Nonlinear Programming (MINLP) problem was solved using the branch-and-bound algorithm. The conceptual designs for multistage countercurrent configuration were derived based on MINLP optimization by comparing results at various conditions. Results showed that at least 3 crystallization stages with keff ≤ 0.4 are required to obtain the 99% (mass fraction) DLTP product within the initial concentration range from10% to 30% (mass fraction).